Identification of Dynamic Active Sites Among Cu Species Derived from MOFs@CuPc for Electrocatalytic Nitrate Reduction Reaction to Ammonia - Ji, Xue‑Yang; Sun, Ke; Liu, Zhi‑Kun; Liu, Xinghui; Dong, Weikang; Zuo, Xintao; Shao, Ruiwen; Tao, Jun (Nano-Micro Letters, 2023)
Direct electrochemical nitrate reduction reaction (NITRR) is a promising strategy to alleviate the unbalanced nitrogen cycle while achieving the electrosynthesis of ammonia. However, the restructuration of the high-activity Cu-based electrocatalysts in the NITRR process has hindered the identification of dynamical active sites and in-depth investigation of the catalytic mechanism. Herein, Cu species (single-atom, clusters, and nanoparticles) with tunable loading supported on N-doped TiO2/C are successfully manufactured with MOFs@CuPc precursors via the pre-anchor and post-pyrolysis strategy. Restructuration behavior among Cu species is co-dependent on the Cu loading and reaction potential, as evidenced by the advanced operando X-ray absorption spectroscopy, and there exists an incompletely reversible transformation of the restructured structure to the initial state. Notably, restructured CuN4&Cu4 deliver the high NH3 yield of 88.2 mmol h−1 gcata−1 and FE ( 94.3%) at − 0.75 V, resulting from the optimal adsorption of NO3− as well as the rapid conversion of *NH2OH to *NH2 intermediates originated from the modulation of charge distribution and d-band center for Cu site. This work not only uncovers CuN4&Cu4 have the promising NITRR but also identifies the dynamic Cu species active sites that play a critical role in the efficient electrocatalytic reduction in nitrate to ammonia. Highlights: 1 Cu species with tunable loading supported on N-doped TiO2/C were successfully fabricated utilizing MOFs@CuPc precursors via the pre-anchor and post-pyrolysis strategy. 2 Cu species with tunable loading supported on N-doped TiO2/C were successfully fabricated utilizing MOFs@CuPc precursors via the pre-anchor and post-pyrolysis strategy. 3 Restructured CuN4&Cu4 performed the highest NH3 yield (88.2 mmol h−1 gcata−1) and FE ( 94.3%) at − 0.75 V due to optimal adsorption of NO3− and rapid conversion of the key intermediates.